Assembly of Palladium(II) and Platinum(II) Metallo‐Rectangles with a Guanosine‐Substituted Terpyridine and Study of Their Interactions with Quadruplex DNA. Issue 16 (5th March 2014) - Ghosh, Sushobhan; Mendoza, Oscar; Cubo, Leticia; Rosu, Frédéric; Gabelica, Valérie; White, Andrew J. P.; Vilar, Ramon
Abstract Two novel [2+2] metallo‐assemblies based on a guanosine‐substituted terpyridine ligand (1) coordinated to palladium(II) (2 a) and platinum(II) (2 b) are reported. These supramolecular assemblies have been fully characterized by NMR spectroscopy, ESI mass spectrometry and elemental analyses. The palladium(II) complex (2 a) has also been characterized by single crystal X‐ray diffraction studies confirming that the system is a [2+2] metallo‐rectangle in the solid state. The stabilities of these [2+2] assemblies in solution have been confirmed by DOSY studies as well as by variable temperature 1H NMR spectroscopy. The ability of these dinuclear complexes to interact with quadruplex and duplex DNA was investigated by fluorescent intercalator displacement (FID) assays, fluorescence resonance energy transfer (FRET) melting studies, and electrospray mass spectrometry (ESI‐MS). These studies have shown that both these assemblies interact selectively with quadruplex DNA (human telomeric DNA and the G‐rich promoter region of c‐myc oncogene) over duplex DNA, and are able to induce dimerization of parallel G‐quadruplex structures.